2010
DOI: 10.1073/pnas.0912437107
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor inhibits CNS autoimmunity by inducing tolerogenic dendritic cells and CD25 + Foxp3 + regulatory T cells

Abstract: Immune-mediated diseases of the CNS, such as multiple sclerosis and its animal model, experimental autoimmune encephalitis (EAE), are characterized by the activation of antigen-presenting cells and the infiltration of autoreactive lymphocytes within the CNS, leading to demyelination, axonal damage, and neurological deficits. Hepatocyte growth factor (HGF) is a pleiotropic factor known for both neuronal and oligodendrocytic protective properties. Here, we assess the effect of a selective overexpression of HGF b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
187
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 174 publications
(209 citation statements)
references
References 52 publications
10
187
1
1
Order By: Relevance
“…Originally identified as a mitogen for hepatocytes, HGF acts as a potent regulator in multiple animal models of immunemediated disorders (7)(8)(9)(10), which suggests that HGF regulates key inflammatory events that are common to many diseases and organ systems. In particular, HGF has been demonstrated to re-strain the Ag-presenting function of mouse DCs (7) and to govern the development of Treg cell-inducing regulatory DCs (11,12). We recently suggested that such a mechanism might account for the protective role of CNS-restricted overexpression of HGF in myelin oligodendrocyte glycoprotein (MOG)-induced EAE (11).…”
Section: Ultiple Sclerosis (Ms) Is a Chronic Disorder Character-mentioning
confidence: 99%
See 2 more Smart Citations
“…Originally identified as a mitogen for hepatocytes, HGF acts as a potent regulator in multiple animal models of immunemediated disorders (7)(8)(9)(10), which suggests that HGF regulates key inflammatory events that are common to many diseases and organ systems. In particular, HGF has been demonstrated to re-strain the Ag-presenting function of mouse DCs (7) and to govern the development of Treg cell-inducing regulatory DCs (11,12). We recently suggested that such a mechanism might account for the protective role of CNS-restricted overexpression of HGF in myelin oligodendrocyte glycoprotein (MOG)-induced EAE (11).…”
Section: Ultiple Sclerosis (Ms) Is a Chronic Disorder Character-mentioning
confidence: 99%
“…In particular, HGF has been demonstrated to re-strain the Ag-presenting function of mouse DCs (7) and to govern the development of Treg cell-inducing regulatory DCs (11,12). We recently suggested that such a mechanism might account for the protective role of CNS-restricted overexpression of HGF in myelin oligodendrocyte glycoprotein (MOG)-induced EAE (11). From an immunologic and therapeutic standpoint, it is important to understand the molecular basis involved in DC immunoregulation by HGF.…”
Section: Ultiple Sclerosis (Ms) Is a Chronic Disorder Character-mentioning
confidence: 99%
See 1 more Smart Citation
“…Mice were kept under pathogen-free conditions and used at 8-10 weeks of age. For active immunization, B6 females were immunized with MOG 35-55 (100 μg) as described (Benkhoucha et al, 2010). Animals received pertussis toxin (300 ng per mouse) on days 0 and 2 after immunization.…”
Section: Mice and Induction Of Eaementioning
confidence: 99%
“…Animals received pertussis toxin (300 ng per mouse) on days 0 and 2 after immunization. Mice were assigned clinical scores daily from 0 to 5 (Benkhoucha et al, 2010). Mice were bled at day 0 (before immunization) and days 7, 14 and 21 after immunization.…”
Section: Mice and Induction Of Eaementioning
confidence: 99%